Multi-choice programming: an overview of theories and applications. (3rd October 2017) - Singh, Shalabh; Sonia
Abstract: This paper presents an exhaustive literature review on theories and applications in the field of multi-choice programming (MCP). The increasing competition in the business world has given rise to the situations where decision-makers are offered with multiple options/information to optimally decide on a single task. Under such circumstances a number of decision-making problems are falling into the scenario of MCPs. Thus, ever-increasing applicability of the MCPs is making more and more Operations Research practitioners to focus on them. This paper analyses all the related work and presents the same by classifying the research problems into two broad categories: theories and applications. As an aid to assist future researchers and practitioners, key insights on the evolution of various variants of MCPs have also been systematically delineated. The paper also throws light on some research gaps and concludes with the scope of future research in this area.